THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE OF PREGNANT MOTHERS ABOUT THE BENEFITS OF ULTRASOUND ON THEIR PREGNANCY AT THE SILAU LAUT PUSKESMAS, SILAU LAUT DISTRICT IN 2021 - Herlia Sumardha Nasution (Science Midwifery, 2022)
One of the pregnancy tests that can be used is Ultrasnography (USG). The mother's willingness to do ultrasound is very dependent on the mother's knowledge and attitude to use ultrasound to determine the development and health of the fetus. This study aims to determine the relationship between knowledge and attitudes of pregnant women about the benefits of ultrasound on pregnancy at the SilauLaut Health Center, SilauLaut District in 2021. This research is a descriptive correlation research with cross sectional approach. This research has been carried out on August 1, 2021 until August 14, 2021. The population is 275 people. Sampling using accidental sampling with a total sample of 34 people. The results showed that the majority of pregnant women's knowledge about the benefits of ultrasound at the SilauLaut Health Center in SilauLaut Sub-district in 2021 was quite good. Sea Glare In 2021 the majority of the second trimester. Based on the results of the chi-square test, it was found that knowledge (p=0.0001<0.05) and attitude (p=0.0001<0.05). The conclusion that’s there is a relationship between knowledge and attitudes of pregnant women about the benefits of ultrasound on pregnancy at the SilauLaut Health Center, SilauLaut District in 2021.The suggestion in this study is that the SilauLaut Health Center provides socialization related to the importance of pregnancy checks and the use of ultrasound so that pregnant women not only assume that the use of ultrasound is only to see gender but can know the health and condition of the fetus.